PROFITABILITY AS MEDIATING ON RELATION BETWEEN FINANCIAL DISTRESS AND FIRM SIZE TO FIRM VALUE IN THE SITUATION OF BEFORE, IN AND AFTER PANDEMIC COVID-19: STUDY CASE PROPERTY AND REAL ESTATE SECTOR (2017-2021) - Anton Adventus Kacaribu; Gregorio Christian Munthe (Jurnal Ekonomi, 2023)
The purpose of this study is to examine the effect of financial distress and firm size on firm value with profitability as intervening/mediating variables. The population of this study was real-estate companies listed on Indonesia Stock Exchange in 2017-2021 that were impacted by when the COVID-19 pandemic occurred. The statistics in this study used Partial Least Square (PLS) based on Structure Equation Model (SEM) Method (SmartPLS3.0). From this study, it can conclude financial distress have an effect on profitability, for financial distress, firm size and profitability do not have an effect on firm value.